2014
DOI: 10.1590/s0100-69162014000100007
|View full text |Cite
|
Sign up to set email alerts
|

Soil chiseling and fertilizer location in sugarcane ratoon cultivation

Abstract: While the pre-harvest sugarcane burning is a disused practice, green harvest requires changes concerning ratoon cultivation due to the presence of a thick layer of straw. The experiment, conducted in a mechanical green harvesting area cultivated with sugarcane, consisted of two stages: in the first stage, the mechanical straw cutting performance of flat disks with different geometry edges was evaluated, considering two types of disks and 10 replications in a completely randomized design; in the second stage, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
0
4
0
2
Order By: Relevance
“…In terms of fertilizer placement, Bianchini et al [19] observed that banded application resulted in higher yields than did broadcast application, whereas Vitti et al [151] found no differences between the two in terms of yield. These results suggest that, so long as N fertilizers are not subject to NH 3 volatilization losses, there is little need for their incorporation in areas under GCTB, and that localized application (usually performed 20-cm distant from the crop row) has advantages because roots are concentrated in the superficial soil layer (0-20 cm) and adjacent to the sugarcane row [157,158].…”
Section: Application Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of fertilizer placement, Bianchini et al [19] observed that banded application resulted in higher yields than did broadcast application, whereas Vitti et al [151] found no differences between the two in terms of yield. These results suggest that, so long as N fertilizers are not subject to NH 3 volatilization losses, there is little need for their incorporation in areas under GCTB, and that localized application (usually performed 20-cm distant from the crop row) has advantages because roots are concentrated in the superficial soil layer (0-20 cm) and adjacent to the sugarcane row [157,158].…”
Section: Application Methodsmentioning
confidence: 99%
“…Maintaining crop residues over soil surfaces brings new challenges, however. The main difficulties caused by a thick layer of trash, when compared with sugarcane fields that were previously burned, related to the incorporation of fertilizers [19], loss of N due to NH 3 volatilization from surfaceapplied urea [20,21], and a higher incidence of pests [22]. Maintenance of trash on the soil surface may also delay sugarcane sprouting during the winter in colder regions, subsequently affecting yields [23].…”
Section: Sugarcane In Brazil: Current Scenariomentioning
confidence: 99%
“…However, sugarcane straw is also a source of biofuel to provide electricity for the sugarcane mills and provides an economic return to the grower when removed from the field. Retention of too much straw on the soil surface also has some disadvantages: it hinders effective mechanical cultivation (Magalhães et al, ) and fertilizer incorporation (Bianchini et al, ), increases the risk of fire during very dry periods (Rossetto, Cantarella, Dias, Landell, & Vitti, ), reduces initial crop tillering (Lisboa et al, ), and encourages pest and disease infestations (Castro et al, ). A sustainable option is to retain 6–8 Mg/ha of the straw residue in the field to provide both economic and environmental benefit and lessen any agronomic disadvantage (Carvalho et al, ).…”
Section: R Options For the Sustainable Management Of P In Sugarcanementioning
confidence: 99%
“…Entretanto, nas quatro socas avaliadas, as produtividades não foram afetadas pela escarificação do solo nas entrelinhas da cultura (Figura 2). De forma análoga, outros trabalhos também não relataram efeito da escarificação de soqueiras na produtividade da cana, em Latossolos de textura média na região norte do Paraná (Paulino et al, 2004), com 260 g kg -1 de argila, e no Mato Grosso (Bianchini et al, 2014), com 252 g kg -1 de argila. Dados de massa específica de raízes foram plotados em função da densidade do solo, do grau de compactação e da resistência mecânica do solo à penetração (Figura 3).…”
Section: Resultsunclassified
“…Ao mesmo tempo, essa prática aumentou o risco de compactação do solo e da degradação de sua estrutura pelo tráfego de colhedoras e transbordos, principalmente em condições de solo úmido (Otto et al, 2011;Souza et al, 2015). A escarificação das entrelinhas em soqueiras de cana-deaçúcar tem sido adotada para a deposição de fertilizantes e para amenizar a compactação do solo (Paulino et al, 2004;Bianchini et al, 2014). Entretanto, a eficiência dessa prática no manejo da compactação do solo e seus efeitos no sistema radicular tem sido motivo de controvérsia (Paulino et al, 2004).…”
unclassified